The Impact Of Flipped Classroom Combined With Problem Based Learning On Learning Motivation And Learning Independent - Abror, Sirojuddin; Rusijono; Arianto, Fajar (Migration Letters, 2024)
This research to investigate the impact of flipped classroom combined with problem based learning on student’s learning motivation. This study used a quasi-experiment with research subjects consisting of sixty-five students at Islamic junior high school who were not randomly selected. The study was conducted by dividing the subjects into two study groups. The study was conducted during 4 meetings in each group to determine the extent of the development of student’s motivation and independent learning. Data collection was carried out using questionnaires, data analysis using normality tests of Kolmogorov-Spirnov tests, homogeneity tests of Levene tests and hypothesis tests using independent sample t-test. The findings in this study showed that the experimental group namely the flipped classroom combined with problem-based learning obtained a higher learning motivation score as well as learning independent one compared to the control group. It is concluded that there is a significant effect of the application of flipped classroom combined with problem-based learning on student’s learning motivation and learning independent at subject of fiqih in Islamic state junior high school 1 Jombang.